The distance of the main and auxiliary openings from the top of medial and distal root of the first lower permanent molar - Jovanović-Medojević Milica; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2005)
The main prerequisite for a successful treatment of pulp disease in apex periodontium is knowledge of morphological characteristics of root canal system, especially one third of his apex. The aim of this work was to define the exact distance of the main and auxiliary openings from the top of medial and distal roots of the first lower permanent molars. Methods: as a research material it was used a hundred extracted first lower molars of the patients of both gender, divided into three age groups. The analysis of the one third of apex was done with the help of binocular magnifying glass and digital roentgenography analysis half of the samples, which were filed with capillary contrast. Results: The results obtained showed that the longest average distance of the main opening from the top of medial root was 0.84mm, and the shortest was 0.61mm; while for the distal root the longest average distance was 0.89mm, and the shortest was 0.62mm. Maximum distance of the auxiliary openings from the top of medial root in the first group was 3.5mm, and the maximum distance of the auxiliary openings from the top of distal root was 2, 5 mm. The results obtained with digital rentgenography showed that the longest average distance of the main opening from the top of medial root was the one noticed in the second age group (0.91mm) then the one from the first group (0,83), and the shortest one in the third age group (0,71mm); as for the distal root: the longest average distance of the main opening from the top of the root was noticed in the third age group (0,95mm) then in the first (0,90mm) and than shortest in the second age group (0,89mm). Conclusion: The distance of the main and auxiliary openings from the top of medial and distal root of the first lower molar varies in the range from 0 to 3,5mm and it depends on the tooth age. .